武汉城市书写与底层女性 ： 以方方与池莉小说为例 = Rewriting Wuhan city and its underclass women - 罗爽 Luo, Shuang (2019)
The rise of Chinese contemporary urban fiction firstly occurred in the 1930s and followed by another outburst in the 1990s. The genre has become an important literary phenomenon with mass writings on different cities, such as Beijing, Shanghai and Wuhan, formed distinguished styles. Unlike Beijing, known as the political centre of China, and Shanghai with the reputation of the wealthiest city in China, Wuhan which locates next to the Yangtze river seems to be a place with ambiguous identities. It once was a significant city during the 1920s but gradually lost its advantages. Two female writers, Fang Fang and Chi Li, who explored the daily life of Wuhan residents and committed to rewriting the city. Both of them uncover the relationship and interactions between the cityscape and underclass women. This paper mainly studies how the city Wuhan and the livings of underclass women were represented in Fang Fang and Chi Li’s works published in recent twenty years. The introduction will explain a few concepts such as New Realism and civil society in the context of China as well as the literature review of research. The second chapter looks into Fang Fang’ fictions on her portray of family conflicts and underclass women running away from home. The third chapter discusses women in public space and how they preserve the city’s spirts through Chi Li’s works. The last chapter draws comparisons between the two writers and reflects on their contrast perspectives.